2009
DOI: 10.1108/02651330910972002
|View full text |Cite
|
Sign up to set email alerts
|

Consumer responses to sex appeal advertising: a cross‐cultural study

Abstract: Purpose -Sex appeal has been widely used in most countries. However, little is known about consumers' responses to sex appeal advertising in different cultures. The purpose of this paper is to examine the effect of sex appeal on ad and brand evaluation among Australian, Chinese and US consumers. Design/methodology/approach -The paper adopted a three (Australia, China and the USA) £ two (male or female model) £ two (low or high level of sex appeal) between-group factorial design. Findings -Australian, Chinese a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 55 publications
2
50
0
Order By: Relevance
“…breasts, bottoms, and chest/belly muscle). A crosscultural study on sex image used in advertising revealed that Chinese consumer had the least positive attitudes when it comes to sex images used in advertising in comparison to the counterparts from USA and Canada (Liu, Cheng, & Li, 2009). Along with the results of this study, it may imply that the image of being "sexy" is less valued by Chinese, and this attitude can be reflected on their selfies.…”
Section: Results and Analysissupporting
confidence: 48%
“…breasts, bottoms, and chest/belly muscle). A crosscultural study on sex image used in advertising revealed that Chinese consumer had the least positive attitudes when it comes to sex images used in advertising in comparison to the counterparts from USA and Canada (Liu, Cheng, & Li, 2009). Along with the results of this study, it may imply that the image of being "sexy" is less valued by Chinese, and this attitude can be reflected on their selfies.…”
Section: Results and Analysissupporting
confidence: 48%
“…Jeon and Beatty (2002) studied comparative advertising effectiveness in different national cultures. Liu et al (2009) addressed consumer responses to sex appeal advertising for a cross-cultural study. They examined the effect of sex appeal on ad and brand evaluation among Australian, Chinese and US consumers and found that Australian, Chinese and US consumers had significantly different attitudes when exposed to the same advertisement but consumer buying intentions towards the advertised brand were not substantially different.…”
Section: Introductionmentioning
confidence: 99%
“…Severn, Belch, & Belch, 1990), gender differences concerning social confirmation and purpose, as well as cultural aspects of nudity in advertising (Beetles & Harris, 2005;Goffman, 1979;Kilbourne, 1999;Liu, Cheng, & Li, 2009;Williamson, 1986), the role of personality in the consumer response to sexual appeals (Black, Organ, & Morton, 2010;Maričić & Radulović, 2013) morality of sexual appeals (Gould, 1994;LaTour & Henthorne, 1994), sexual imagery and portrayal of women in magazine ads (Kang, 1997;Reichert, 2003; Thompson, 2000), emotional response to male nudity (Reichert, Lambiase, Morgan, Carstarphen, & Zavoina, 1999; Simpson, Horton, & Brown, 1996) and male responses only to the use of sexual themes (Grazer & Kessling, 2011). Based on the existing types of sexual content in advertising (nudity, sexual behaviour, physical attractiveness, sexual reference and sexual embeds) this research builds on previous paper (see Autor, 2012) to explore the effects of sexual appeal in print ads related to semiotic codes.…”
Section: Introductionmentioning
confidence: 99%